Plan de negocio para la exportación de mango liofilizado a la Unión Europea (2017)
This document presents a business plan for the export of lyophilized mango. Where, in the first place, the present opportunity for this sector is presented and the market situation is described both in Colombia and in the European Union. Technical parameters of the project were established, including a detailed description of the lyophilization process together with the necessary machinery to carry out fruit processing, followed by a financial analysis and cost evaluation to know the feasibility of the project; and to conclude, the strategies for the export and commercialization of the product in the European Union were established.